Pyroprotein-based electronic textiles with high thermal durability. Issue 9 (November 2018) - Jeon, Jun Woo; Oh, Joo Young; Cho, Se Youn; Lee, Sungho; Jang, Hyun-Seok; Jung, Won Taek; Kim, Jeong-Gyun; Kim, Hyeonbeom; Kim, Hyuk Jin; Kim, SeongYeon; Han, Songlee; Kim, JunHo; et al.
Graphical abstract: Abstract: Electronic textiles (e-textiles) need to have high heat durability for various applications. However, current e-textiles are usually damaged by high-temperature processes. We report silk-based e-textiles fabricated by simple pyrolysis with axial stretching that demonstrate high electrical conductivity and thermal durability. The electrical conductivity of the proposed e-textiles was on the order of 10 3 S/cm and the electrical characteristics were maintained even after heating and bending. Furthermore, we prepared e-textiles with various electronic properties, such as semiconducting, superconducting, and light-emitting properties, by depositing ZnO, MoSe2, and NbN onto the commercial silk-based e-textiles using sputtering and evaporation. We introduced a simple method for fabricating silk-based e-textiles with various electronic properties, which are compatible with the current textile industry.